Focused ion beam machining of hard materials for micro engineering applications - Evans, R. (Cranfield University, 2009)
The Focused Ion Beam (FIB) milling of single crystal diamond was investigated and the beam drift and mill yield were quantified. The effect of water assistance on the milling of diamond was found to double the yield. The surface morphology that spontaneously forms during milling was measured and the mechanisms behind its formation investigated. The effect of gallium implantation on the diamond crystal structure was measured by x-ray diffraction. Chemical vapour deposited polycrystalline diamond (PCD) has been machined into micro scale turning tools using a combination of laser processing and FIB machining. Laser processing was used to machine PCD into rounded tool blanks and then the FIB was used to produce sharp cutting edges. This combines the volume removal ability of the laser with the small volume but high precision ability of the FIB. Turning tools with cutting edges of 39µm and 13µm were produced and tested by machining micro channels into oxygen free high conductivity copper (OFHCC). The best surface quality achieved was 28nm Sq. This is compared to a Sq of 69nm for a commercial PCD tool tested under the same circumstances. The 28nm roughness compares well to other published work that has reported a Ra of 20nm when machining OFHCC with single crystal diamond tools produced by FIB machining. The time taken to FIB machine a turning tool from a lasered blank was approximately 6.5 hours. Improvements to the machining process and set up have been suggested that should reduce this to ~1 hour, making this a more cost effective process. PCD tools with sinusoidal cutting prongs were produced using FIB. The dimensions of the prongs were less than 10µm. The tools were tested in OFHCC and the prongs survived intact. Changes to the machining conditions are suggested for improved replication of the prongs into metal. Sapphire was FIB machined to produce nano and micro patterns on a curved surface. The sapphire is part of a micro injection mould for replication of polymer parts. The comparative economics of hot embossing and injection moulding have been studied. Injection moulding was found to be the more cost effective process for making polymer parts at commercial production levels.